Implementasi Pengamanan File Rekam Medis Pada Puskesmas Perlayuan - Ritonga, Aldi Rapandi; Irmayani, Deci; Ritonga, Ali Akbar (Politeknik Ganesha Medan, 2022)
This study aims to provide an effort to secure files in order to maintain important documents as assets for the Perlayuan Health Center. The Perlayuan Health Center is one of the world's health units whose role is to support health and the security of medical record files. Important factual documents that have been recorded regarding the historical history of symptoms and diseases that have been recorded such as disease or illness conditions, prevention or healing techniques that have been carried out and have been missed have previously been documented by the Health service at the Perlayuan Health Center. Medical records have or keep important records that are documented with data in the form of patient identities, examinations, treatment, actions from the facilitators of the Perlayuan Health Center. Rivest's Cipher 6 method is used to lock files. The medical record aims to be an initial benchmark to continue the action plan for drugs and treatments that will be applied. File security with At the Perlayuan Health Center there is very little security for a file because each data is not only stored on one computer and if needed the file will be copied to anyone who asks for the file. That way the file is no longer guaranteed security and confidentiality. Anyone can easily retrieve files by copying formatted encryption or data encryption. Rivest's Cipher 6 algorithm can break 128 bits blocks into 4 sets of 32 bits and this algorithm can work with 4 32 bits registers X, B, Y and D.